(untitled) (Journal of Forest and Livelihood, 2004)
Increasing demand of bark of Lokta (Daphne bholua and D. papyracea) and Argeli (Edgeworthia gardneri) for subsistence as well as commercial use demands more careful assessment of resource base and application of sustainable harvesting techniques to ensure the sustainability of local hand made paper enterprises. A systematic inventory of Lokta and Argeli would determine the resource availability and annual harvestable yields. Based on the case study of central hills of Nepal, this paper demonstrates the need for incorporating ecological integrity, economical viability, and social acceptability to define the sustainable management of Lokta, which can in turn ensure the sustainability of hand made paper enterprises.